Why do self-referent cues facilitate mathematical word problem-solving? Insights from eye tracking - Joshua J. March; Janet F. McLean; Josephine Ross; Jan R. Kuipers; Sheila J. Cunningham (PLoS ONE, 2026)
Associating information with the self enhances processing of that information, with simple text cues like self-referent pronouns (i.e., ‘You’) increasing response speed and accuracy in processing tasks. Research suggests this can be applied in educational contexts, such as children’s mathematical word problem-solving. Whilst children show faster and more accurate word problem-solving when self-pronouns are included in the text, the mechanisms underlying these effects are unclear. The current study extends previous research by using eye-tracking to monitor 9- to 11-year-old children’s processing during mathematical word problem-solving. Children were faster to solve subtraction problems that contained a self-referential pronoun, but this was not the case for addition problems. Eye tracking data revealed that faster processing time was driven by reduced fixation length on referent information in the self-pronoun problems across problem types: children spent less time looking at self-pronouns than terms referring to another person (e.g., character names). This suggests that self-pronouns may facilitate problem-solving by supporting active storage of items bound to self in working memory, reducing the need for revisitation during mathematical word-problem solving. This is likely to be particularly beneficial for more cognitively challenging problems, providing an explanation for patterns of self-reference effects reported previously.